2010
DOI: 10.1007/s11240-010-9812-7
|View full text |Cite
|
Sign up to set email alerts
|

Shoot organogenesis and somatic embryogenesis from leaf and shoot explants of Ochna integerrima (Lour)

Abstract: Ochna integerrima is a medicinal and ornamental plant in Southeastern Asia. It has been listed as a rare and endangered species in China. Here we studied the effects of plant growth regulators and their concentrations on the induction of somatic embryogenesis and shoot organogenesis from leaf and shoot explants of O. integerrima for the first time. Cytokinins played a crucial role in somatic embryogenesis and shoot organogenesis. Among them, a higher concentration of thidiazuron (10.0-15.0 lM TDZ) could induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…With respect to the culture media, we used the growth regulator TDZ (at 0.9 μM) to induce the embryogenesis in two media that differed in their salt and vitamin composition. This growth regulator was used in the present work since it may increase direct organogenesis and embryogenesis (Gisbert et al, 2006;Chhabra et al, 2008;Ma et al, 2011). Our results show that the salts and vitamins also influenced callus formation, because a higher percentage of direct embryogenesis was obtained in EIM2 compared to EIM1.…”
mentioning
confidence: 67%
“…With respect to the culture media, we used the growth regulator TDZ (at 0.9 μM) to induce the embryogenesis in two media that differed in their salt and vitamin composition. This growth regulator was used in the present work since it may increase direct organogenesis and embryogenesis (Gisbert et al, 2006;Chhabra et al, 2008;Ma et al, 2011). Our results show that the salts and vitamins also influenced callus formation, because a higher percentage of direct embryogenesis was obtained in EIM2 compared to EIM1.…”
mentioning
confidence: 67%
“…Error bars indicate 95 % CI multiple shoot regeneration. Similarly, Ma et al (2011) indicated that TDZ has a stronger effect on callus induction and shoot organogenesis than BAP in Ochna integerrima. TDZ can act as a substitute for both the auxin and cytokinin requirements for in vitro morphogenesis (organogenesis and somatic embryogenesis) in several species (Murthy et al 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Spontaneous adventitious root formation has been reported in Tuberaria major and Dierama erectum (Goncalves et al 2010;Kothe et al 2010). Difficulties with root induction have also been observed in B. sinuspersici in vitro (Rosnow et al 2011) and in in vitro shoots of Ochna integerrima and Pityopsis ruthii (Ma et al 2011;Wadl et al 2011). The poor rooting ability of these studies may be attributed to the accumulation of metabolic products of BA such as BA9G (Werbrouck et al 1995(Werbrouck et al , 1996Bairu et al 2008).…”
Section: Discussionmentioning
confidence: 99%